A Qualitative System Dynamic Modelling on Sustainable Tourism Development (Case Study: Depok Beach at Bantul Regency) - Nuryadin, Didi; Sodik, Jamzani; Artaningtyas, Wahyu Dwi (RSF Conference Series: Business, Management and Social Sciences, 2021)
Depok beach is a tourism destination located in Yogyakarta’s south coastal area with its unique attractions. The tourism development at Depok beach finds some problems, especially on tourism sustainability. This research tried to model a system for managing Depok beach as a sustainable tourist attraction. System dynamics were used for modeling the management strategy. The data of this study were gathered by doing observation and in-depth interviews with related stakeholders. This research found that the Depok beach management model is a complex system consisting of social, economic, and ecological subsystems. The management system of Depok beach was quite nice, even one environmental aspect, which is waste management was not fully appropriate. Locals waste management was done traditionally, neglecting any ecological problems that may be occurred. The optimization of Depok beach management might be achieved by strengthening the waste management system.